2020
DOI: 10.1016/j.ajo.2020.03.042
|View full text |Cite
|
Sign up to set email alerts
|

Role of Deep Learning–Quantified Hyperreflective Foci for the Prediction of Geographic Atrophy Progression

Abstract: To quantitatively measure hyperreflective foci (HRF) during the progression of geographic atrophy (GA) secondary to age-related macular degeneration (AMD) using deep learning (DL) and investigate the association with local and global growth of GA.METHODS: Eyes with GA were prospectively included. Spectral-domain optical coherence tomography (SDOCT) and fundus autofluorescence images were acquired every 6 months. A 500-mm-wide junctional zone adjacent to the GA border was delineated and HRF were quantified usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 71 publications
(76 reference statements)
1
47
0
1
Order By: Relevance
“…Three publications used AI to predict future spatial GA progression: Niu et al, Pfau et al, and Schmidt-Erfurth et al 45 47 Niu et al and Schmidt-Erfurth et al both combined segmentation with progression modeling. Niu et al 45 utilized their previously published Chan-Vese model and added a random forest with 100 trees to build its prediction model using 19 extracted features.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three publications used AI to predict future spatial GA progression: Niu et al, Pfau et al, and Schmidt-Erfurth et al 45 47 Niu et al and Schmidt-Erfurth et al both combined segmentation with progression modeling. Niu et al 45 utilized their previously published Chan-Vese model and added a random forest with 100 trees to build its prediction model using 19 extracted features.…”
Section: Resultsmentioning
confidence: 99%
“…Schmidt-Erfurth and colleagues used a residual U-Net for their segmentation and a linear regression for their progression modeling. 47 Results from the segmentation were not available. They found that hyper-reflective foci (HRF) concentration was positively correlated with GA progression in unifocal and multifocal GA (all P < 0.001) and de-novo GA development ( P = 0.037).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, a plethora of progression risk factors have been described in the setting of GA [78]. This includes, amongst other characteristics (e.g., the described vascular alterations), the fundus autofluorescence phenotype [6], baseline lesion size [79], lesion shape [28, 80], and structural OCT characteristics, such as incomplete outer retinal atrophy [81, 82], lesion boundary configuration [83], reticular drusen [84], and hyperreflective foci [85]. Based on clinical experience and preliminary data, these imaging features provide correlated/redundant information.…”
Section: Future Directionsmentioning
confidence: 99%